ISLAM DAN TRANSFORMASI BUDAYA LOKAL DI INDONESIA - Moh. Teguh Prasetyo (Batuthah: Jurnal Sejarah Padaban Islam, 2023)
The spread of Islam in Indonesia is not only limited to religious aspects, but also includes values, norms and cultural practices. Islam brought changes in various aspects of life, such as art, language, architecture and ways of dressing. Each region has its own distinct local culture, and Islam has played a role in integrating these cultural elements into the broader Islamic context. For example, the Javanese art of wayang kulit combines Islamic elements in the performance of Hindu epic stories, creating a unique art form that reflects the integration of Islam and local culture. This research method uses the cultural history method with four research stages, namely, first, searching for documents, second, criticizing documents, third, interpreting or interpreting, and fourth, presentation in the form of historiography. The results of this research reveal how Islam also influences social norms and values in Indonesia. For example, the concepts of gotong royong (collective cooperation) and Musyawarah (consultation) which are an important part of Indonesian culture, are also influenced by Islamic values of social solidarity and consensus in decision making. As well as influencing the style of aspects of art and architecture in Indonesia.